Impact of Climate Change in Eastern Madhya Pradesh, India. (August 2013) - Sushant,
This paper reports case studies in eastern Madhya Pradesh – a central Indian province – on community adaptation strategies for sustainable livelihood options. With about 90% of the region being rain-fed, erratic rainfalls in the last fifteen years have caused up to a 60% decrease in crop yields, directly impacting the food security of the region. The System of Rice Intensification (SRI) and horticultural expansion are adaptation measures for tackling climate change. The expansion of kitchen gardens from subsistence-level to commercial-level is another significant development in the region. Meanwhile, increased pressure on common lands has caused fuelwood scarcity for households and decreased livestock fodder. While output of most non-timber forest products (NTFPs) has reduced drastically due to unsustainable extraction, production of mahua ( Madhuca indica ) has not suffered as much, thanks to a community-managed user regime. Community-based institutions have the potential to support the ecosystem-based livelihoods of forest-dependent communities.